High-temperature-resistant UV viscosity-reducing film and preparation method thereof
By using modified monomers and fillers in UV adhesives, high-temperature-resistant UV adhesive films are prepared, and PET optical film and release film are coated on the PE protective film, the UV adhesive is solved at high temperature and ultraviolet Adhesion problems under light achieve good durability and tack reduction effect.
Patent Information
- Application Number
- CN202411573799.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-20
AI Technical Summary
At this stage, the adhesion of UV adhesive reduces in high temperature environments, and the adhesion is not obvious after ultraviolet light irradiation, which affects the use effect.
Using modified monomers, bishydroxypolydimethylsiloxane, bisphenylmethane diisocyanate and modified fillers, high temperature resistant UV viscosity-reducing glue is prepared through specific reaction steps, and coated on the PE protective film. PET optical film and release film form a high-temperature resistant UV mucosa.
It significantly improves the durability of UV mucosa in high temperature environments, and achieves the effect of reducing adhesion and decoction reduction through cross-linking reaction and photogenerating electron transfer after ultraviolet light, and meets the use under high temperature and UV conditions. need.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of UV viscosity-reducing adhesive preparation, and in particular to a high-temperature resistant UV viscosity-reducing film and a preparation method thereof. Background Art
[0002] With the continuous development of information technology and the semiconductor industry, the demand for various wafer-based devices is increasing. Anti-viscosity film is one of the key materials for wafer processing. Anti-viscosity film, also known as anti-viscosity tape, is made by coating anti-viscosity adhesive on substrates such as polyester film and polyolefin film. In addition to the processing of semiconductor round materials, the cutting of ultra-thin glass and the acid treatment of glass such as mobile phone screens all require anti-viscosity film. Anti-viscosity film plays a fixed and protective role when processing easily damaged materials to prevent splashing fragments and breakage: after the processing is completed, in order to facilitate the picking up of the processed parts, the curing and anti-viscosity effect greatly reduces the adhesion of the anti-viscosity film, and the processed parts are separated from the substrate, and then the next step of processing is carried out. However, at this stage, the temperature resistance of the anti-viscosity adhesive is general, and the adhesion will be significantly reduced in a high temperature environment. The adhesion of some anti-viscosity adhesives does not decrease significantly after ultraviolet light irradiation, which affects normal use. Summary of the invention
[0003] The purpose of the present invention is to provide a high temperature resistant UV anti-viscosity film and a preparation method thereof, which solves the problem that the adhesion of the current UV anti-viscosity film decreases under high temperature environment and the anti-viscosity effect is not obvious under UV irradiation.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high temperature resistant UV anti-viscosity film, specifically comprising the following steps: coating a printable coating on one side of a PE protective film, covering a PET optical film on the printable coating, coating a high temperature resistant UV anti-viscosity adhesive on the PET optical film, and covering a release film on the high temperature resistant UV anti-viscosity adhesive to obtain a high temperature resistant UV anti-viscosity film; The high temperature resistant UV viscosity reducing adhesive is made by the following steps: The modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF are mixed, nitrogen is introduced for protection, and the modified filler is added under the conditions of a rotation speed of 120-150r / min and a temperature of 60-70°C. After reacting for 3-4 hours, 1,4-butanediol is added, and the reaction is continued for 3-4 hours. The temperature is lowered to 20-25°C, 1-hydroxycyclohexyl phenyl ketone is added, and the mixture is stirred evenly to obtain a high temperature resistant UV viscosity reducing adhesive.
[0005] Furthermore, the amount ratio of the modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, DMF and modified filler is 6 mol: 4 mol: 15 mmol: 20 mL: 50 mg, the molecular weight of dihydroxy polydimethylsiloxane is 2000, the amount of dibutyltin dilaurate is 1% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate, the amount of 1,4-butanediol is 10% of the mass of the modified monomer, and the amount of 1-hydroxycyclohexyl phenyl ketone is 3% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate.
[0006] Further, the modified monomer is prepared by the following steps: Step A1: 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene and N,N-dimethylacetamide are uniformly mixed, nitrogen is introduced for protection, p-chlorobenzonitrile is added under stirring at a speed of 120-150 r / min and a temperature of 50-60° C., the temperature is raised to 175-180° C., and the reaction is carried out for 15-20 hours to obtain intermediate 1, intermediate 1, potassium hydroxide, ethanol and deionized water are uniformly mixed, and the reaction is carried out at a speed of 200-300 r / min and a temperature of 80-85° C. for 20-25 hours to obtain intermediate 2; Step A2: Intermediate 2, diethanolamine, dicyclohexylcarbodiimide and toluene are mixed, and reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of 30-40°C to obtain intermediate 3. Intermediate 3, triethylamine, 4-tert-butylcatechol and tetrahydrofuran are mixed evenly, and nitrogen is introduced for protection. Fumaryl chloride is added under stirring at a speed of 120-150 r / min and a temperature of 3-5°C, and the temperature is raised to 25-30°C. The reaction is carried out for 2-3 hours to obtain a modified monomer.
[0007] Furthermore, the amount ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene, N,N-dimethylacetamide and p-chlorobenzonitrile described in step A1 is 10mmol:25mmol:12mL:20mL:22mmol, and the amount ratio of intermediate 1, potassium hydroxide, ethanol and deionized water is 5mmol:1mL:1mL:10mmol.
[0008] Furthermore, the molar ratio of the intermediate 2, diethanolamine and dicyclohexylcarbodiimide described in step A2 is 1:2:2.1, and the amount ratio of the intermediate 3, triethylamine, 4-tert-butylcatechol, tetrahydrofuran and fumaryl chloride is 10mmol:16mmol:3mg:4mL:8mmol.
[0009] Further, the modified filler is prepared by the following steps: Step B1: Triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and under the conditions of a rotation speed of 150-200 r / min and a temperature of 80-85° C., tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol are added with stirring, and the reaction is carried out for 4-6 hours, and the supernatant is removed by centrifugation, and the substrate is placed in a muffle furnace, and calcined for 3-3.5 hours at a temperature of 600-650° C. in a nitrogen atmosphere to obtain a composite carrier; Step B2: p-nitrobenzaldehyde and propionic acid are mixed, stirred and refluxed at a speed of 120-150 r / min and a temperature of 140-145° C., and pyrrole is added to react for 2-3 hours to obtain nitroporphyrin. Nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution are mixed uniformly, reacted at a speed of 150-200 r / min and a temperature of 65-70° C. for 1-2 hours, and the pH value is adjusted to be alkaline to obtain aminoporphyrin. Aminoporphyrin, KH560 and DMF are mixed uniformly, reacted at a speed of 200-300 r / min, a temperature of 30-40° C. and a pH value of 10-11 for 4-6 hours to obtain an organic ligand; Step B3: The organic ligand and anhydrous dichloromethane are mixed evenly, nitrogen is introduced for protection, and zinc acetate is added under stirring at a speed of 60-80 r / min and a temperature of 40-45°C. After reacting for 2-3 hours, the filtrate is removed by filtration, the substrate is dispersed in ethanol, the composite carrier is added, and ultrasonic treatment is performed for 10-15 minutes at a frequency of 20-30 kHz and a temperature of 50-60°C. Deionized water is added and the reaction is performed for 3-5 hours to obtain a modified filler.
[0010] Furthermore, the usage ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol in step B1 is 13 mg:76 mg:110 mg:5 mL:2 mmol:12 mmol:1 mmol:1 mL.
[0011] Furthermore, the dosage ratio of p-nitrobenzaldehyde, propionic acid and pyrrole in step B2 is 6 mmol:25 mL:6 mmol, the dosage ratio of nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution is 0.25 g:1 g:15 mL, the mass fraction of concentrated hydrochloric acid solution is 36%, and the molar ratio of aminoporphyrin and KH560 is 1:4.
[0012] Furthermore, the amount ratio of the organic ligand, anhydrous dichloromethane, zinc acetate and composite carrier described in step B3 is 0.4g:50mL:1g:0.1g.
[0013] Beneficial effects of the present invention: A high-temperature resistant UV anti-viscosity film prepared by the present invention is prepared by coating a printable coating on one side of a PE protective film, covering the printable coating with a PET optical film, coating a high-temperature resistant UV anti-viscosity adhesive on the PET optical film, and covering the high-temperature resistant UV anti-viscosity adhesive with a release film. The high-temperature resistant UV anti-viscosity adhesive is reacted with a modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate to form a prepolymer, which is then reacted with a modified filler and 1,4-butanediol in sequence, and 1-hydroxycyclohexyl phenyl ketone is added and mixed to prepare the high-temperature resistant UV anti-viscosity adhesive.
[0014] The modified monomer is prepared by reacting 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one as a raw material with potassium carbonate to form a salt, and then reacting with the chlorine atom site of p-chlorobenzonitrile to obtain an intermediate 1, hydrolyzing the intermediate 1 under the action of potassium hydroxide to convert the nitrile group into a carboxyl group to obtain an intermediate 2, reacting the intermediate 2 with ethylene glycol amine under the action of dicyclohexylcarbodiimide to make the carboxyl group on the intermediate 2 react with the secondary amine on the ethylene glycol amine to obtain an intermediate 3, and reacting the intermediate 3 with fumaryl chloride to make the hydroxyl group on the intermediate 3 react with the acyl chloride group on the fumaryl chloride to obtain a hyperbranched alcohol structure, thereby obtaining the modified monomer.
[0015] The modified filler is prepared by hydrolyzing and condensing ethyl orthosilicate, tetrabutyl titanate and boric acid as raw materials, and then calcining to form porous borosilicate-doped titanium dioxide to obtain a composite carrier, reacting nitrobenzoic acid with pyrrole to obtain nitroporphyrin, reducing the nitroporphyrin to convert the nitro group into ankylosing to obtain aminoporphyrin, reacting the aminoporphyrin with KH560 to make the amino group on the aminoporphyrin react with KH560 to obtain an organic ligand, reacting the organic ligand with zinc acetate under anhydrous conditions to form a zinc organic framework, and then ultrasonicating the composite carrier in deionized water to obtain a modified filler.
[0016] The modified monomer contains a naphthobiphenyl structure, which reacts with dihydroxy polydimethylsiloxane, so that the prepared UV viscosity-reducing adhesive has good high temperature resistance. At the same time, the modified monomer is a hyperbranched structure, and each branch chain contains a large number of unsaturated double bonds. After being irradiated with ultraviolet rays, the unsaturated double bonds undergo a cross-linking reaction to form an interpenetrating grid structure, which causes the volume of the UV viscosity-reducing adhesive to shrink, thereby reducing the adhesion. The modified filler is a porous structure with a large specific surface area, and contains an organic framework of boron-doped titanium dioxide and zinc, which can promote the transfer of photogenerated electrons and holes, thereby improving the catalytic effect of the modified filler, and the surface porphyrin structure can promote the breaking of chemical bonds in the UV viscosity-reducing adhesive molecules, thereby destroying their integrity and then oxidizing with oxygen in the air to achieve a viscosity-reducing effect. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1
[0019] A method for preparing a high temperature resistant UV anti-viscosity film, specifically comprising the following steps: coating a printable coating on one side of a PE protective film, covering a PET optical film on the printable coating, coating a high temperature resistant UV anti-viscosity adhesive on the PET optical film, and covering a release film on the high temperature resistant UV anti-viscosity adhesive to obtain a high temperature resistant UV anti-viscosity film; The high temperature resistant UV viscosity reducing adhesive is made by the following steps: The modified monomer, dihydroxypolydimethylsiloxane, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF were mixed, nitrogen was introduced for protection, and the modified filler was added under the conditions of a rotation speed of 120r / min and a temperature of 60°C. After reacting for 3 hours, 1,4-butanediol was added and the reaction was continued for 3 hours. The temperature was lowered to 20°C, 1-hydroxycyclohexyl phenyl ketone was added, and the mixture was stirred evenly to obtain a high temperature resistant UV viscosity reducing adhesive.
[0020] The amount ratio of the modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, DMF and modified filler is 6 mol: 4 mol: 15 mmol: 20 mL: 50 mg, the molecular weight of dihydroxy polydimethylsiloxane is 2000, the amount of dibutyltin dilaurate is 1% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate, the amount of 1,4-butanediol is 10% of the mass of the modified monomer, and the amount of 1-hydroxycyclohexyl phenyl ketone is 3% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate.
[0021] The modified monomer is prepared by the following steps: Step A1: 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene and N,N-dimethylacetamide were mixed uniformly, nitrogen was introduced for protection, p-chlorobenzonitrile was added under stirring at a speed of 120 r / min and a temperature of 50° C., and the temperature was raised to 175° C. to react for 15 h to obtain intermediate 1, intermediate 1, potassium hydroxide, ethanol and deionized water were mixed uniformly, and the reaction was carried out at a speed of 200 r / min and a temperature of 80° C. for 20 h to obtain intermediate 2; Step A2: Intermediate 2, diethanolamine, dicyclohexylcarbodiimide and toluene are mixed, and the reaction is carried out at a speed of 150 r / min and a temperature of 30°C for 3 hours to obtain intermediate 3. Intermediate 3, triethylamine, 4-tert-butylcatechol and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, fumaryl chloride is added under stirring at a speed of 120 r / min and a temperature of 3°C, the temperature is raised to 25°C, and the reaction is carried out for 2 hours to obtain a modified monomer.
[0022] The amount ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene, N,N-dimethylacetamide and p-chlorobenzonitrile described in step A1 is 10mmol:25mmol:12mL:20mL:22mmol, and the amount ratio of intermediate 1, potassium hydroxide, ethanol and deionized water is 5mmol:1mL:1mL:10mmol.
[0023] The molar ratio of intermediate 2, diethanolamine and dicyclohexylcarbodiimide described in step A2 is 1:2:2.1, and the amount ratio of intermediate 3, triethylamine, 4-tert-butylcatechol, tetrahydrofuran and fumaryl chloride is 10mmol:16mmol:3mg:4mL:8mmol.
[0024] The modified filler is prepared by the following steps: Step B1: Triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and ethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol are added under stirring at a speed of 150 r / min and a temperature of 80° C. After reacting for 4 hours, the supernatant is removed by centrifugation, and the substrate is placed in a muffle furnace and calcined for 3 hours at a temperature of 600° C. in a nitrogen atmosphere to obtain a composite carrier; Step B2: p-nitrobenzaldehyde and propionic acid are mixed, stirred and refluxed at a speed of 120 r / min and a temperature of 140° C., and pyrrole is added to react for 2 h to obtain nitroporphyrin. Nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution are mixed evenly, reacted at a speed of 150 r / min and a temperature of 65° C. for 1 h, and the pH value is adjusted to be alkaline to obtain aminoporphyrin. Aminoporphyrin, KH560 and DMF are mixed evenly, reacted at a speed of 200 r / min, a temperature of 30° C. and a pH value of 10 for 4 h to obtain an organic ligand; Step B3: The organic ligand and anhydrous dichloromethane are mixed evenly, nitrogen is introduced for protection, and zinc acetate is added under stirring at a speed of 60 r / min and a temperature of 40°C. After reacting for 2 hours, the filtrate is removed by filtration, the substrate is dispersed in ethanol, the composite carrier is added, ultrasonic treatment is performed for 10 minutes at a frequency of 20 kHz and a temperature of 50°C, deionized water is added, and the reaction is performed for 3 hours to obtain a modified filler.
[0025] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol described in step B1 is 13 mg:76 mg:110 mg:5 mL:2 mmol:12 mmol:1 mmol:1 mL.
[0026] The amount ratio of p-nitrobenzaldehyde, propionic acid and pyrrole described in step B2 is 6mmol:25mL:6mmol, the amount ratio of nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution is 0.25g:1g:15mL, the mass fraction of concentrated hydrochloric acid solution is 36%, and the molar ratio of aminoporphyrin and KH560 is 1:4.
[0027] The amount ratio of the organic ligand, anhydrous dichloromethane, zinc acetate and composite carrier described in step B3 is 0.4g:50mL:1g:0.1g.
[0028] Example 2
[0029] A method for preparing a high temperature resistant UV anti-viscosity film, specifically comprising the following steps: coating a printable coating on one side of a PE protective film, covering a PET optical film on the printable coating, coating a high temperature resistant UV anti-viscosity adhesive on the PET optical film, and covering a release film on the high temperature resistant UV anti-viscosity adhesive to obtain a high temperature resistant UV anti-viscosity film; The high temperature resistant UV viscosity reducing adhesive is made by the following steps: The modified monomer, dihydroxypolydimethylsiloxane, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF were mixed, nitrogen was introduced for protection, and the modified filler was added under the conditions of a rotation speed of 120r / min and a temperature of 65°C. After reacting for 4 hours, 1,4-butanediol was added and the reaction was continued for 3 hours. The temperature was lowered to 20°C, 1-hydroxycyclohexyl phenyl ketone was added, and the mixture was stirred evenly to obtain a high temperature resistant UV viscosity reducing adhesive.
[0030] The amount ratio of the modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, DMF and modified filler is 6 mol: 4 mol: 15 mmol: 20 mL: 50 mg, the molecular weight of dihydroxy polydimethylsiloxane is 2000, the amount of dibutyltin dilaurate is 1% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate, the amount of 1,4-butanediol is 10% of the mass of the modified monomer, and the amount of 1-hydroxycyclohexyl phenyl ketone is 3% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate.
[0031] The modified monomer is prepared by the following steps: Step A1: 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene and N,N-dimethylacetamide were mixed uniformly, nitrogen was introduced for protection, p-chlorobenzonitrile was added under stirring at a speed of 120 r / min and a temperature of 55° C., the temperature was raised to 175° C., and the reaction was carried out for 18 hours to obtain intermediate 1, intermediate 1, potassium hydroxide, ethanol and deionized water were mixed uniformly, and the reaction was carried out at a speed of 200 r / min and a temperature of 85° C. for 20 hours to obtain intermediate 2; Step A2: Intermediate 2, diethanolamine, dicyclohexylcarbodiimide and toluene are mixed, and the reaction is carried out at a speed of 150 r / min and a temperature of 35°C for 4 hours to obtain intermediate 3. Intermediate 3, triethylamine, 4-tert-butylcatechol and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, fumaryl chloride is added under stirring at a speed of 120 r / min and a temperature of 4°C, the temperature is raised to 25°C, and the reaction is carried out for 3 hours to obtain a modified monomer.
[0032] The amount ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene, N,N-dimethylacetamide and p-chlorobenzonitrile described in step A1 is 10mmol:25mmol:12mL:20mL:22mmol, and the amount ratio of intermediate 1, potassium hydroxide, ethanol and deionized water is 5mmol:1mL:1mL:10mmol.
[0033] The molar ratio of intermediate 2, diethanolamine and dicyclohexylcarbodiimide described in step A2 is 1:2:2.1, and the amount ratio of intermediate 3, triethylamine, 4-tert-butylcatechol, tetrahydrofuran and fumaryl chloride is 10mmol:16mmol:3mg:4mL:8mmol.
[0034] The modified filler is prepared by the following steps: Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and under the conditions of a rotation speed of 150 r / min and a temperature of 85° C., tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol are added with stirring, and the reaction is carried out for 5 hours, and the supernatant is removed by centrifugation, and the substrate is placed in a muffle furnace, and calcined for 3.5 hours at a temperature of 630° C. in a nitrogen atmosphere to obtain a composite carrier; Step B2: p-nitrobenzaldehyde and propionic acid are mixed, stirred and refluxed at a speed of 120 r / min and a temperature of 145° C., and pyrrole is added to react for 2.5 hours to obtain nitroporphyrin. Nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution are mixed evenly, reacted at a speed of 150 r / min and a temperature of 70° C. for 1.5 hours, and the pH value is adjusted to be alkaline to obtain aminoporphyrin. Aminoporphyrin, KH560 and DMF are mixed evenly, reacted at a speed of 200 r / min, a temperature of 35° C. and a pH value of 11 for 5 hours to obtain an organic ligand; Step B3: The organic ligand and anhydrous dichloromethane are mixed evenly, nitrogen is introduced for protection, and zinc acetate is added under stirring at a speed of 80 r / min and a temperature of 40°C. After reacting for 2 hours, the filtrate is removed by filtration, the substrate is dispersed in ethanol, the composite carrier is added, and ultrasonic treatment is performed for 15 minutes at a frequency of 25 kHz and a temperature of 55°C. Deionized water is added and the reaction is performed for 4 hours to obtain a modified filler.
[0035] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol described in step B1 is 13 mg:76 mg:110 mg:5 mL:2 mmol:12 mmol:1 mmol:1 mL.
[0036] The amount ratio of p-nitrobenzaldehyde, propionic acid and pyrrole described in step B2 is 6mmol:25mL:6mmol, the amount ratio of nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution is 0.25g:1g:15mL, the mass fraction of concentrated hydrochloric acid solution is 36%, and the molar ratio of aminoporphyrin and KH560 is 1:4.
[0037] The amount ratio of the organic ligand, anhydrous dichloromethane, zinc acetate and composite carrier described in step B3 is 0.4g:50mL:1g:0.1g.
[0038] Example 3
[0039] A method for preparing a high temperature resistant UV anti-viscosity film, specifically comprising the following steps: coating a printable coating on one side of a PE protective film, covering a PET optical film on the printable coating, coating a high temperature resistant UV anti-viscosity adhesive on the PET optical film, and covering a release film on the high temperature resistant UV anti-viscosity adhesive to obtain a high temperature resistant UV anti-viscosity film; The high temperature resistant UV viscosity reducing adhesive is made by the following steps: The modified monomer, dihydroxypolydimethylsiloxane, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF were mixed, nitrogen was introduced for protection, and the modified filler was added under the conditions of a rotation speed of 150r / min and a temperature of 70°C. After reacting for 4 hours, 1,4-butanediol was added and the reaction was continued for 4 hours. The temperature was lowered to 25°C, 1-hydroxycyclohexyl phenyl ketone was added, and the mixture was stirred evenly to obtain a high temperature resistant UV viscosity reducing adhesive.
[0040] The amount ratio of the modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, DMF and modified filler is 6 mol: 4 mol: 15 mmol: 20 mL: 50 mg, the molecular weight of dihydroxy polydimethylsiloxane is 2000, the amount of dibutyltin dilaurate is 1% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate, the amount of 1,4-butanediol is 10% of the mass of the modified monomer, and the amount of 1-hydroxycyclohexyl phenyl ketone is 3% of the total mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate.
[0041] The modified monomer is prepared by the following steps: Step A1: 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene and N,N-dimethylacetamide were mixed uniformly, nitrogen was introduced for protection, p-chlorobenzonitrile was added under stirring at a speed of 150 r / min and a temperature of 60° C., the temperature was raised to 180° C., and the reaction was carried out for 20 h to obtain intermediate 1; intermediate 1, potassium hydroxide, ethanol and deionized water were mixed uniformly, and the reaction was carried out at a speed of 300 r / min and a temperature of 85° C. for 25 h to obtain intermediate 2; Step A2: Intermediate 2, diethanolamine, dicyclohexylcarbodiimide and toluene are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 40°C for 5 hours to obtain intermediate 3. Intermediate 3, triethylamine, 4-tert-butylcatechol and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, fumaryl chloride is added under stirring at a speed of 150 r / min and a temperature of 5°C, the temperature is raised to 30°C, and the reaction is carried out for 3 hours to obtain a modified monomer.
[0042] The amount ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene, N,N-dimethylacetamide and p-chlorobenzonitrile described in step A1 is 10mmol:25mmol:12mL:20mL:22mmol, and the amount ratio of intermediate 1, potassium hydroxide, ethanol and deionized water is 5mmol:1mL:1mL:10mmol.
[0043] The molar ratio of intermediate 2, diethanolamine and dicyclohexylcarbodiimide described in step A2 is 1:2:2.1, and the amount ratio of intermediate 3, triethylamine, 4-tert-butylcatechol, tetrahydrofuran and fumaryl chloride is 10mmol:16mmol:3mg:4mL:8mmol.
[0044] The modified filler is prepared by the following steps: Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and under the conditions of a rotation speed of 200 r / min and a temperature of 85° C., tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol are added with stirring, and the reaction is carried out for 6 hours, and the supernatant is removed by centrifugation, and the substrate is placed in a muffle furnace, and calcined for 3.5 hours at a temperature of 650° C. in a nitrogen atmosphere to obtain a composite carrier; Step B2: p-nitrobenzaldehyde and propionic acid are mixed, stirred and refluxed at a speed of 150 r / min and a temperature of 145° C., and pyrrole is added to react for 3 hours to obtain nitroporphyrin. Nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution are mixed evenly, reacted at a speed of 200 r / min and a temperature of 70° C. for 2 hours, and the pH value is adjusted to be alkaline to obtain aminoporphyrin. Aminoporphyrin, KH560 and DMF are mixed evenly, reacted at a speed of 300 r / min, a temperature of 40° C. and a pH value of 11 for 6 hours to obtain an organic ligand; Step B3: The organic ligand and anhydrous dichloromethane are mixed evenly, nitrogen is introduced for protection, and zinc acetate is added under stirring at a speed of 80 r / min and a temperature of 45°C. After reacting for 3 hours, the filtrate is removed by filtration, the substrate is dispersed in ethanol, the composite carrier is added, ultrasonic treatment is performed for 15 minutes at a frequency of 30 kHz and a temperature of 60°C, deionized water is added, and the reaction is performed for 5 hours to obtain a modified filler.
[0045] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol described in step B1 is 13 mg:76 mg:110 mg:5 mL:2 mmol:12 mmol:1 mmol:1 mL.
[0046] The amount ratio of p-nitrobenzaldehyde, propionic acid and pyrrole described in step B2 is 6mmol:25mL:6mmol, the amount ratio of nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution is 0.25g:1g:15mL, the mass fraction of concentrated hydrochloric acid solution is 36%, and the molar ratio of aminoporphyrin and KH560 is 1:4.
[0047] The amount ratio of the organic ligand, anhydrous dichloromethane, zinc acetate and composite carrier described in step B3 is 0.4g:50mL:1g:0.1g.
[0048] Comparative Example 1 Compared with Example 1, no dihydroxy polydimethylsiloxane was added in this comparative example, and the remaining steps were the same.
[0049] Comparative Example 2 Compared with Example 1, this comparative example uses 1,8-octanediol to replace intermediate 3, and the remaining steps are the same.
[0050] Comparative Example 3 Compared with Example 1, no composite carrier was added in this comparative example, and the remaining steps were the same.
[0051] Comparative Example 4 Compared with Example 1, titanium dioxide is used to replace the modified filler in this comparative example, and the other steps are the same.
[0052] Comparative Example 5 Compared with Example 1, no modified filler was added in this comparative example, and the remaining steps were the same.
[0053] The high temperature resistant UV anti-viscosity films prepared in Examples 1-3 and Comparative Examples 1-5 were made into 200mm×25mm, and in accordance with the standard of GB / T2792-2014, the tensile rate was 300mm / min, and the 180° peel strength test was carried out at room temperature, 100°C and 150°C, respectively. Then, UV curing was performed for 60s, and the peel strength was tested at room temperature. The test results are shown in the following table.
[0054]
[0055] It can be seen from the above table that the present application has a good high temperature resistance effect, and the viscosity reduction effect is obvious after UV irradiation.
[0056] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant UV viscosity reducing film, characterized in that: Specifically, the method comprises the following steps: coating a printable coating on one side of a PE protective film, covering a PET optical film on the printable coating, coating a high temperature resistant UV viscosity reducing adhesive on the PET optical film, and covering a release film on the high temperature resistant UV viscosity reducing adhesive to obtain a high temperature resistant UV viscosity reducing film; The high temperature resistant UV viscosity reducing adhesive is made by the following steps: The modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF are mixed, nitrogen is introduced for protection, and the modified filler is added after stirring. After the reaction, 1,4-butanediol is added, and the reaction is continued. The temperature is lowered and 1-hydroxycyclohexyl phenyl ketone is added. The mixture is stirred evenly to obtain a high temperature resistant UV viscosity reducing adhesive.
2. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 1, characterized in that: The amount ratio of the modified monomer, dihydroxy polydimethylsiloxane, diphenylmethane diisocyanate, DMF and modified filler is 6 mol: 4 mol: 15 mmol: 20 mL: 50 mg, the amount of 1,4-butanediol is 10% of the mass of the modified monomer, and the amount of 1-hydroxycyclohexyl phenone is 3% of the mass of the modified monomer, dihydroxy polydimethylsiloxane and diphenylmethane diisocyanate.
3. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step A1: 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene and N,N-dimethylacetamide are uniformly mixed, nitrogen is introduced for protection, p-chlorobenzonitrile is added while stirring, and the temperature is raised to react to obtain intermediate 1; intermediate 1, potassium hydroxide, ethanol and deionized water are mixed to react to obtain intermediate 2; Step A2: Intermediate 2, diethanolamine, dicyclohexylcarbodiimide and toluene are mixed and reacted to obtain intermediate 3, intermediate 3, triethylamine, 4-tert-butylcatechol and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, fumaryl chloride is added while stirring, and the temperature is raised to react to obtain a modified monomer.
4. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 3, characterized in that: The amount ratio of 4-(4-hydroxyphenyl)-2,3-naphthyridin-1-one, potassium carbonate, toluene, N,N-dimethylacetamide and p-chlorobenzonitrile described in step A1 is 10mmol:25mmol:12mL:20mL:22mmol, and the amount ratio of intermediate 1, potassium hydroxide, ethanol and deionized water is 5mmol:1mL:1mL:10mmol.
5. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 3, characterized in that: The molar ratio of intermediate 2, diethanolamine and dicyclohexylcarbodiimide described in step A2 is 1:2:2.1, and the amount ratio of intermediate 3, triethylamine, 4-tert-butylcatechol, tetrahydrofuran and fumaryl chloride is 10mmol:16mmol:3mg:4mL:8mmol.
6. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are mixed and stirred, and tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol are added, and after reaction, the supernatant is removed by centrifugation, and the substrate is placed in a muffle furnace and calcined to obtain a composite carrier; Step B2: p-nitrobenzaldehyde and propionic acid are mixed, stirred and refluxed, and pyrrole is added to react to obtain nitroporphyrin, nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution are mixed to react, and the pH value is adjusted to be alkaline to obtain aminoporphyrin, and aminoporphyrin, KH560 and DMF are mixed to react to obtain an organic ligand; Step B3: The organic ligand and anhydrous dichloromethane are mixed evenly, nitrogen is introduced for protection, zinc acetate is added after stirring, the reaction is carried out, the filtrate is removed by filtering, the substrate is dispersed in ethanol, the composite carrier is added, ultrasonic treatment is carried out, deionized water is added, and the reaction is carried out to obtain a modified filler.
7. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 6, characterized in that: The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, tetrabutyl titanate, boric acid and ethanol described in step B1 is 13 mg:76 mg:110 mg:5 mL:2 mmol:12 mmol:1 mmol:1 mL.
8. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 6, characterized in that: The amount ratio of p-nitrobenzaldehyde, propionic acid and pyrrole described in step B2 is 6mmol:25mL:6mmol, the amount ratio of nitroporphyrin, stannous chloride and concentrated hydrochloric acid solution is 0.25g:1g:15mL, and the molar ratio of aminoporphyrin and KH560 is 1:
4.
9. The method for preparing a high temperature resistant UV viscosity reducing film according to claim 6, characterized in that: The amount ratio of the organic ligand, anhydrous dichloromethane, zinc acetate and composite carrier described in step B3 is 0.4g:50mL:1g:0.1g.
10. A high temperature resistant UV anti-viscosity film, characterized in that: Prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
UV viscosity-reducing adhesive and preparation method thereof
CN113698908A
UV viscosity-reducing adhesive for electronic device manufacturing process and preparation method of UV viscosity-reducing adhesive
CN116536023A
Weather-resistant epoxy-based structural adhesive and preparation method thereof
CN116589960A
Graphene oxide / metal composite material and preparation method thereof
CN116682947A
How to specify the ball release position in screen golf
KR102602364B1
